Seni Film Sebagai Sarana Dakwah Dalam Perspektif Al-Qur'an (Analisis Film 5 PM dengan Teori Semiotika Roland Barthes) - Izharul Haq; Nurbaiti Nurbaiti; Abd. Muid Nawawi (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
The current digital Era has challenges for preachers in using effective and targeted da'wah media. Unfortunately, the information and content of Da'wah spread on the internet sometimes has not been verified, so it can cause confusion and misunderstanding among the public. The purpose of this study is to examine the film 5 PM (5 corners of the mosque) as a medium of Da'wah in the perspective of the Qur'an by using Roland Barthes semiotic analysis. Roland Barthes semiotic analysis in this study managed to explain how the message of Da'wah conveyed through this film. The method in this study uses qualitative methods with documentation techniques, library research, maudhi tafsir and case studies to collect and analyze data. The Data used in this study is the film 5 PM (5 corners of the mosque) produced by Beda Sinema Pictures in 2018. The results of this study that the film 5 PM (5 corners of the mosque) has succeeded in becoming an effective da'wah media. This can be seen from the theme and message of Da'wah conveyed through the film. This Film is also able to reach various levels of society and produce a positive impact in increasing awareness and understanding of the religion of Islam. The theme of the film 5 PM (5 corners of the mosque) has strong relevance to verse 125 of Surah an-Nahl in the Qur'an. The verse teaches Muslims to do da'wah in a wise and gentle way.